2018
DOI: 10.5114/aic.2018.78325
|View full text |Cite
|
Sign up to set email alerts
|

Acute, total occlusion of the left main stem: coronary intervention options, outcomes, and recommendations

Abstract: IntroductionAcute, total occlusion of the unprotected left main stem (uLMo) in acute coronary syndrome (ACS) patients is a catastrophic event often accompanied by sudden cardiac death (SCD) and/or cardiogenic shock (CS) with high mortality rates and limited methods of successful treatment. Emergent, surgical and percutaneous revascularization has been reported before, yet comprehensive data remains scarce.AimTo examine emergency percutaneous coronary intervention (PCI) outcomes in ACS cases presenting with uLM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 17 publications
2
22
0
3
Order By: Relevance
“…ST-segment elevation in aVR and/or V1 and widespread ST-segment depression usually raises the suspicion of LMCA occlusion [ 8 ]. Cardiogenic shock is the most common complication of LMCA occlusion, it may present in more than 85% of cases [ 9 ], and therefore, it also indicates LMCA occlusion. The mortality rate is high with LMCA occlusion compared to lesions in other vessels and >50% of patients require CPR at some point [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…ST-segment elevation in aVR and/or V1 and widespread ST-segment depression usually raises the suspicion of LMCA occlusion [ 8 ]. Cardiogenic shock is the most common complication of LMCA occlusion, it may present in more than 85% of cases [ 9 ], and therefore, it also indicates LMCA occlusion. The mortality rate is high with LMCA occlusion compared to lesions in other vessels and >50% of patients require CPR at some point [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of cardiogenic shock in such patients can be as high as 50%, and is a significant independent predictor of mortality. 5,6 Patients with myocardial infarction complicated with cardiogenic shock are commonly treated with IABP. However, previous studies have suggested that placement of an IABP in AMI patients with cardiogenic shock under coronary angiography does not reduce the incidence of major adverse cardiovascular events, and is significantly associated with increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Паттерн ИМпST -это подъем ST в прекордиальных отведениях в сочетании с элевацией в aVR [4,26] или без нее [9] при окклюзии СтЛКА в отсутствие коллатерального кровотока. Данная ЭКГ-картина встречается в 37,5% всех случаев верифицированной тромботической окклюзии СтЛКА [10].…”
Section: экг-паттерн импSt при остром поражении стлкаunclassified
“…СтЛКА обеспечивает кровоснабжение 75% массы левого желудочка (ЛЖ) у пациентов с "правым" или "сбалансированным" типом кровоснабжения и 100% в случае "левого" типа. В связи с этим тяжёлые поражения СтЛКА приводят к нарушению кровоснабжения большей части миокарда ЛЖ с высоким риском угрожающих жизни событий, связанных с дисфункцией ЛЖ, фатальными аритмиями [1][2][3][4][5].…”
unclassified
See 1 more Smart Citation